Sympathetic innervation of interscapular brown adipose tissue is not a predominant mediator of Oxytocin (OT)-elicited reductions of body weight gain and adiposity in male diet-induced obese rats - Edwards, Melise M.; Nguyen, Ha K.; Dodson, Andrew D.; Herbertson, Adam J.; Honeycutt, Mackenzie K.; Slattery, Jared D.; Rambousek, June R.; Tsui, Edison; Wolden-Hanson, Tami; Wietecha, Tomasz A.; Graham, James L.; Tapia, Geronimo P.; et al. (Frontiers in Drug Delivery, 2024)
Recent studies indicate that central administration of oxytocin (OT) reduces body weight (BW) in high fat diet-induced obese (DIO) rodents by reducing energy intake and increasing energy expenditure (EE). Previous studies in our lab have shown that administration of OT into the fourth ventricle (4V; hindbrain) elicits weight loss and stimulates interscapular brown adipose tissue temperature (TIBAT) in DIO rats. We hypothesized that OT-elicited stimulation of sympathetic nervous system (SNS) activation of IBAT contributes to its ability to activate BAT and reduce BW in DIO rats. To test this, we determined the effect of disrupting SNS activation of IBAT on OT-elicited stimulation of TIBAT and reduction of BW in DIO rats. We first confirmed that bilateral surgical SNS denervation to IBAT was successful based on having achieved ≥60% reduction in IBAT norepinephrine (NE) content from DIO rats. NE content was selectively reduced in IBAT by 94.7 ± 2.7, 96.8% ± 1.8% and 85.9% ± 6.1% (p < 0.05) at 1, 6 and 7 week post-denervation, respectively, and was unchanged in liver or inguinal white adipose tissue. We then measured the impact of bilateral surgical SNS denervation to IBAT on the ability of acute 4V OT (1, 5 µg) to stimulate TIBAT in DIO rats. We found that the high dose of 4V OT (5 µg) stimulated TIBAT similarly between sham and denervated rats (P=NS) and that the effects of 4V OT to stimulate TIBAT did not require beta-3 adrenergic receptor signaling. We subsequently measured the effect of bilateral surgical denervation of IBAT on the effect of chronic 4V OT (16 nmol/day) or vehicle infusion to reduce BW, adiposity, and energy intake in DIO rats. Chronic 4V OT reduced BW gain by −7.2 ± 9.6 g and −14.1 ± 8.8 g in sham and denervated rats (p < 0.05 vs. vehicle treatment), respectively, and this effect was similar between groups (P=NS). These effects were associated with reductions in adiposity and energy intake (p < 0.05). Collectively, these findings support the hypothesis that sympathetic innervation of IBAT is not required for central OT to increase BAT thermogenesis and reduce BW gain and adiposity in male DIO rats.